PENGARUH MODAL KERJA, NILAI UPAH, DAN TEKNOLOGI TERHADAP PENYERAPAN TENAGA KERJA PADA INDUSTRI KERAJINAN SERAT AGEL DI DESA SALAMREJO - Uwi Martayadi; Dyah Indraswati (Sekolah Tinggi Pariwisata Mataram, 2021)
The objectives to be achieved in this research are to 1). Knowing the effect of working capital on labor absorption 2). Knowing the effect of wages on labor absorption 3). Knowing the effect of technology on labor absorption 4). Knowing the effect of working capital, wage value and technology simultaneously on the absorption of labor in the agel fiber handicraft industry in Salamrejo Village, Sentolo District, Kulon Progo. This type of research is Expost Facto research. This research is causal associative because it looks for the influence of independent variables on the dependent variable. The population in this study were all agel fiber handicraft entrepreneurs in the village of Salamrejo, which according to the head of the development division in the village of Salamrejo were 30 entrepreneurs. The data collection methods used questionnaires, interviews, and documentation. The analysis used is multiple linear regression. The results showed that there was a positive and significant influence between working capital on labor absorption. There is a positive and significant influence between the value of wages on labor absorption. There is a positive and significant influence between technology on labor absorption. There is a positive and significant influence between working capital, wages and technology simultaneously on labor absorption in Salamrejo Village in December 2019.